2020
DOI: 10.3390/v12111343
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Method for Detection of Arbovirus Infection of Saliva in Mosquitoes Aedes aegypti and Ae. albopictus

Abstract: Vector competence refers to the ability of a vector to acquire, maintain, and transmit a pathogen. Collecting mosquito saliva in medium-filled capillary tubes has become the standard for approximating arbovirus transmission. However, this method is time-consuming and labor-intensive. Here we compare the capillary tube method to an alternative high-throughput detection method the collection of saliva on paper cards saturated with honey, with (FTA card) and without (filter paper) reagents for the preservation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
2
0
2
Order By: Relevance
“…Além disso, é importante destacar que, em casos de epidemias como as provocadas pelas doenças veiculadas pelo Aedes aegypti, os surtos epidêmicos também possuem uma forte relação com os fatores intrínsecos do mosquito, tais como plasticidade comportamental, rápido desenvolvimento, resistência dos ovos à dessecação, competência vetorial para várias arboviroses e antropofilia (adaptação aos hábitos humanos), sendo necessário que as ações de controle levem em conta cada um destes aspectos (HONÓRIO et al, 2020). Tais fatores não foram considerados pelos alunos nas suas respostas, verificando que eles depositavam toda confiança nas ações de controle e contenção de responsabilidade dos órgãos públicos, bem como nos cientistas.…”
Section: Resultsunclassified
“…Além disso, é importante destacar que, em casos de epidemias como as provocadas pelas doenças veiculadas pelo Aedes aegypti, os surtos epidêmicos também possuem uma forte relação com os fatores intrínsecos do mosquito, tais como plasticidade comportamental, rápido desenvolvimento, resistência dos ovos à dessecação, competência vetorial para várias arboviroses e antropofilia (adaptação aos hábitos humanos), sendo necessário que as ações de controle levem em conta cada um destes aspectos (HONÓRIO et al, 2020). Tais fatores não foram considerados pelos alunos nas suas respostas, verificando que eles depositavam toda confiança nas ações de controle e contenção de responsabilidade dos órgãos públicos, bem como nos cientistas.…”
Section: Resultsunclassified
“…The titer of infectious virus in a mosquito is potentially of epidemiological importance because there is likely a positive correlation between virus titer in the mosquito and transmission risk. For example, in a study examining infection of Aedes aegypti by another alphavirus, chikungunya virus, it was found that for each 10-fold increase in viral titer in the mosquito legs there was a 49% increase in the probability of detecting virus in the saliva [14]. Interestingly, numerous studies have documented that there is often extensive variation in arbovirus titer between individual mosquitoes after being given an infectious blood meal.…”
Section: Introductionmentioning
confidence: 99%
“…É importante destacar que essas epidemias também possuem uma forte relação com os fatores intrínsecos do vetor Aedes aegypti, tais como, plasticidade comportamental, rápido desenvolvimento, resistência dos ovos à dessecação, competência vetorial para várias arboviroses e antropofilia (adaptação aos hábitos humanos) sendo necessário que as ações de controle levem em conta cada um destes aspectos (Carvalho & Moreira 2017;Honório et al, 2020;Aragão et al, 2019;Mukherjee et al, 2019).…”
Section: Introductionunclassified